Immunomodulation for the Treatment of Fungal Infections: Opportunities and Challenges - Muluneh Ademe (Frontiers in Cellular and Infection Microbiology, 2020)
Opportunistic fungal infections are major causes of morbidity and mortality in patients with single or multiple defects in their immunity. Antifungal agents targeting the pathogen remain the treatment of choice for fungal infections. However, antifungal agents are toxic to the host mainly due to the close evolutionary similarity of fungi and humans. Moreover, antifungal therapy is ineffective in patients with immunosuppression. For this reason, there is an increased demand to develop novel strategies to enhance immune function and augment the existing antifungal drugs. In recent times, targeting the immune system to improve impaired host immune responses becomes a reasonable approach to improve the effectiveness of antifungal drugs. In this regard, immunomodulating therapeutic agents that turn up the immune response in the fight against fungal infections hold promise for enhancing the efficacy and safety of conventional antifungal therapy. In general, immunomodulating therapies are safe with decreased risk of resistance and broad spectrum of activity. In this review, therefore, clinical evidences supporting the opportunities and challenges of immunomodulation therapies in the treatment of invasive fungal infections are included.